ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI PRICE TO BOOK VALUE SAHAM PADA BANK DEVISA YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2013-2014 - Shelly Karina Diani; Dyah Fitriani (Jurnal Fokus Manajemen Bisnis, 2016)
This study aims to examine what factors affect the Price to Book Value (PBV) of shares in foreign exchange banks listed on the Indonesia Stock Exchange in the period 2013-2014 using indicators of CAR (Capital Adequacy Ratio), NPL (Non Performing) financial ratios Loans), LDR (Loan to Deposit ratio), Net Interst Margin (NIM), ROE (Return on Equity) and BOPO (Operating costs per Operating income) as independent variables and PBV (Price to Book Value) as the dependent variable. The sample used in this study amounted to 19 foreign exchange banks listed on the Indonesia Stock Exchange (IDX) for the 2013-2014 period. The statistical tool used to test the effect of the independent variable partially on the dependent variable is the T test, while to test the effect of the independent variable on the dependent variable simultaneously the F test is used. The results of this study indicate that the partial test results of the T test are the first variable, namely Capital Adequacy Ratio (CAR) with a value of 0.019 significantly influences the Price to Book Value of banking industry shares, the second variable Non Performing Loans (NPL) with a value of 0.018 significantly influences the Price to Book Value of banking industry shares, the third variable is Loan to Dept Ratio (LDR) with the value of 0,000 has a significant effect on the Price to Book Value of the banking industry shares, the fourth variable Net Interest Margin (NIM) with a value of 0.003 has a significant effect on the Price to Book Value of the banking industry shares, then the fifth variable Return on Equity (ROE) with a value of 0.080 has no significant effect against Price to Book Value of banking industry shares, and the sixth variable Operational Cost per Operating Income (BOPO) with a value of 0.002 has a significant effect on Price to Book Value of banking industry shares.